Criminology Analysis of Women's as Perpetrators of Domestic Violence Crimes - Ismail, Dian Ekawaty; Sarson, Mohamad Taufiq Zulfikar (Jambura Law Review, 2021)
This study aims to find out the analysis of women's criminology as perpetrators of domestic violence crimes. This research is a combination of Normative law research with prescriptive analysis techniques. As for approach is the approach of legislation (statute approach) and case approach. The results showed that factors that affect the number of acts of violence against husbands in the household, namely, economic factors, communication factors, factors of low understanding of religion in the household, factors of parents, husbands often consume alcohol, the presence of a third person in the household as well as psychological factors. Efforts made by law enforcement officials to tackle domestic violence crimes committed by women in Gorontalo city, namely, preventive countermeasures, curative countermeasures, and repressive efforts carried out at the crime time. In making this effort, the police must take action in case of domestic violence cases.